KONFLIK PERTAMBANGAN EMAS TANPA IZIN (PETI) DI DESA PETAPAHAN KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - ", Al Zuhri; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in Kuantan Singingi in order to obtain information about Gold Mining Conflicts Without Permission (illegal). Some of the problems in this study were (1) What form of gold mining conflicts without permission (illegal) in the village of Petapahan? (2) What are the causes of conflict gold mining without permission (illegal) in the village of Petapahan? (3) Who are the actors of conflict gold mining without permission (illegal) in the village of Petapahan ?. The title of this research is the "Gold Mining Conflicts Without Permission (illegal) In the village of Gunung Toar Petapahan Regency Kuantan Singingi". This research aims to find out To find out how to shape the conflict that occurred in the village especially Petapahan against illegal gold mining (PETI). To find out what the causes of conflict gold mining without permission (illegal) in the village of Petapahan. To find out who the actors gold mining conflict without permission (illegal) in the village of Petapahan. This research is qualitative because it is shaped case, which was the subject of this study is determined by those who know and are involved directly in the conflict as much as 9 subjects Mining. In collecting the data, engineering data collection using interviews, observation, and documentation. To analyze the problems in this study using qualitative analysis as well as will be described in descriptive in doing the writing. After peThis research has, the survey results revealed that the shape of the gold mining conflict without permission (illegal) in the village of Petapahan are demonstrations, arson camp, throwing cars dompeng and government, conflict and the horizontal and vertical conflicts caused by environmental factors, economic factors, factors of land, and social factors. Actors of the conflict that the ark of investors or financiers who have the interests of individuals or groups to profit or mining products as much as possible and in order to achieve its objectives. The presence of conflict, the causes of conflict and conflict actor So that trigger conflict gold mining without permission (illegal) in the village of Petapahan.Keywords: Conflict, Gold Mining